Rethinking ovary preservation by adnexal torsion reversal in adolescents: a case of delayed diagnosis - Yue He; Chen Ji; Xiao-Chang Shen; Ke-Xin Zhang; Yu-Mei Wu; Yan Wang (BMC, 2022)
Abstract Background This article discusses the management of an adolescent woman with a delayed diagnosis of adnexal torsion (AT) whose ovaries were successfully preserved. Case presentation The patient was a 14-year-old female teen admitted with the chief complaint of lower abdominal pain for 3 days and worsening pain for 2 days. Magnetic resonance imaging suggested a high possibility of torsion in the anterosuperior uterine mass and was accompanied by severe ovarian edema, bleeding, and enlargement. Intraoperatively, the left fallopian tube was characterized by thickening and torsion and appeared blackish purple. The left fallopian tube paraovarian cyst was about 20 cm in size, and the left adnexa was twisted 1080° along the left infundibulopelvic ligament (suspensory ligament of the left ovary). The left ovary appeared blackish purple, with an enlarged diameter of about 10 cm. At the request and with the informed consent of the patient's parents, we preserved the left ovary and removed the left fallopian tube. The results of the endocrine, ultrasound, and tumor marker tests were normal 1 month after surgery. Follicles and blood flow signals seen in ultrasound examinations indirectly proved the successful preservation of the left ovary in the follow-up. Conclusions Our attempt to preserve the ovaries in an adolescent with a delayed diagnosis of AT was successful.